Strategi Bank Syariah Indonesia Mempertahankan Nasabah Melalui Handling Complaint Di BSI KCP Purwokerto - Sulasih, Sulasih; Intansari, Anggita isty; Novandari, Weni (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Customer Service is a very important aspect in the banking world. Therefore, banks must focus on providing services to customers. Because good service is a bank's strategy to retain its customers. This study aims to describe the Strategy of Bank Syariah Indonesia to Retain Customers Through Handling Complaints at BSI KCP Purwokerto through the role of customer service in handling complaints in order to retain customers. The type of field research with a qualitative descriptive approach. Data collection techniques consist of observation, interviews, and documentation. This study uses data collection methods, data reduction, data presentation, and drawing conclusions as data analysis techniques. The results of this study indicate that customer service plays a very important role. The role of customer service in handling complaints is as a channel for problem information and solution services. To retain customers, customer service must provide friendly service, approach, and really look for solutions and alternatives to solve problems that occur so that customers feel comfortable and satisfied. So that it can retain customers, both new and old customers